Diversity and Species Composition of Phyco-Periphyton on Some Macrophytes in Rafin Makaranta Stream, Bauchi - Magaji, Hafsat M.; Ezra, A.G.; Deba, F.A. (International Journal of Scientific Research in Biological Sciences, 2024)
Water quality is essential to human health due to its direct influence on ecosystems and public health. This study analyzed selected physicochemical parameters and the phyco-periphyton assemblage on aquatic macrophytes in Rafin Makaranta Stream, Bauchi, Nigeria, from February to September 2021 at four sampling sites. The objectives were to evaluate the stream`s physical, chemical, and biological characteristics. Phyco-periphyton samples were collected by carefully cutting aquatic macrophytes with a sharp razor blade and preserving them in 4% formalin. Standard methods were used to analyze physicochemical parameters, which showed ranges for temperature (24.5 - 34.9°C), pH (7.2 - 8.9), conductivity (0.46 - 0.67 µS/cm), total dissolved solids (338 - 472 mg/L), dissolved oxygen (2.09 - 7.2 mg/L), biochemical oxygen demand (0.66 - 3.67 mg/L), total suspended solids (0.1 - 0.3 mg/L), turbidity (20 - 162 NTU), nitrate (0.2 - 16.7 mg/L), and phosphate (0.1 - 0.9 mg/L). Principal Component Analysis (PCA) indicated that biochemical oxygen demand had the greatest positive environmental impact, followed by total dissolved solids and temperature. Additionally, Pearson correlation showed a positive association between total dissolved solids, temperature, and turbidity, suggesting their combined effect on water quality dynamics. Six macrophytes, including Nymphaea lotus (18.18%), Ludwigia abyssinica (9.09%), Hygrophila auriculata (18.18%), Pistia stratiotes (27.27%), and Typha domingensis (18.18%), served as essential habitats for the periphyton community. The periphyton identified comprised four classes: Bacillariophyta (6 genera), Chlorophyta (11 genera), Cyanophyta (7 genera), and Euglenophyta (3 genera), with Chlorophyta being dominant at 44%, followed by Cyanophyta (39%), Bacillariophyta (12%), and Euglenophyta (5%). Notable nutrient enrichment indicators, including Melosira, Scenedesmus, Oscillatoria, and Anabaena, were observed. Canonical Correspondence Analysis highlighted temperature, total dissolved solids, biochemical oxygen demand, and dissolved oxygen as significant physicochemical factors affecting the structure, composition, and distribution of the periphytic community. Overall, the findings suggest that Rafin Makaranta Stream is impacted by both natural and human-related factors, which influence its algal community and contribute to water contamination. Continued monitoring is recommended to confirm these findings and effectively manage potential environmental impacts.